2023
DOI: 10.3390/cells12071024
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Synthesized Indoloquinoline Analog to Isolates from Cryptolepis sanguinolenta on Tumor Growth Inhibition and Hepatotoxicity in Ehrlich Solid Tumor-Bearing Female Mice

Abstract: The study evaluated the antitumor efficacy of APAN, “synthesized indoloquinoline analog derived from the parent neocryptolepine isolated from the roots of Cryptolepis sanguinolenta”, versus the chemotherapeutic drug etoposide (ETO) in Ehrlich solid tumor (EST)-bearing female mice as well as its protective effect against etoposide-triggered hepatic disorders. APAN showed an ameliorative activity against Ehrlich solid tumor and hepatic toxicity, and the greatest improvement was found in the combined treatment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 61 publications
(69 reference statements)
1
3
0
Order By: Relevance
“…In-silico screening of the quinoline based compounds revealed their promising affinity to Topoisomerase II which is consistent with studies done on similar compounds as acridine and neocryptolipines 61 . The proposed binding mode of the investigated compounds showed marked affinity values ranging from a maximum value of -6.5392 kcal/mol recorded by 7e and a minimum value of -5.5638 kcal/mol recorded by 7c .…”
Section: Resultssupporting
confidence: 85%
“…In-silico screening of the quinoline based compounds revealed their promising affinity to Topoisomerase II which is consistent with studies done on similar compounds as acridine and neocryptolipines 61 . The proposed binding mode of the investigated compounds showed marked affinity values ranging from a maximum value of -6.5392 kcal/mol recorded by 7e and a minimum value of -5.5638 kcal/mol recorded by 7c .…”
Section: Resultssupporting
confidence: 85%
“…These results parallel previous investigations indicating the proliferation and metastasis of carcinoma cells into many internal organs [ 40 ]. The inflammatory cellular infiltrates responsible for hepatic inflammation progression may be attributed to mitochondrial damage [ 44 , 45 , 46 ] or the harmful effects of tumor angiogenesis caused by proangiogenic factor secretion [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the antitumor activity of TAM against breast cancer by blocking estrogen receptors, inhibiting angiogenesis, and increasing apoptosis [ 53 , 54 ]. Our study is parallel to previous reports that showed the antitumor activity of ORL [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ,…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α is a cytokine that plays a vital role in immunity, protection, and inflammation. It is also associated with tumor progression and carcinogenesis [ 25 ]. Our findings show that echinacoside significantly reduced the overexpression of both NFκB and TNF-α induced by ESC.…”
Section: Discussionmentioning
confidence: 99%